2012
DOI: 10.1101/sqb.2012.77.015115
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Nuclear Suppression of Host Immunity by Effectors from the Arabidopsis Downy Mildew Pathogen Hyaloperonospora arabidopsidis (Hpa)

Abstract: Filamentous phytopathogens form sophisticated intracellular feeding structures called haustoria in plant cells. Pathogen effectors are likely to play a role in the establishment and maintenance of haustoria additional to their more characterized role of suppressing plant defense. Recent studies suggest that effectors may manipulate host transcription or other nuclear regulatory components for the benefit of pathogen development. However, the specific mechanisms by which these effectors promote susceptibility r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…A significant number of host-targeted pathogen effector proteins localize entirely to host cell nuclei, indicating active nuclear import or passive diffusion through the NPC and sequestration in the nucleus (Deslandes and Rivas, 2011; Caillaud et al, 2012a,b). Generally, nuclear localization correlates with NLS motifs in the primary sequence suggesting that these effectors exploit the host cell’s nuclear import machinery for nuclear translocation.…”
Section: Hold On Tight - Nuclear Pathogen Effectors and The Importin-mentioning
confidence: 99%
“…A significant number of host-targeted pathogen effector proteins localize entirely to host cell nuclei, indicating active nuclear import or passive diffusion through the NPC and sequestration in the nucleus (Deslandes and Rivas, 2011; Caillaud et al, 2012a,b). Generally, nuclear localization correlates with NLS motifs in the primary sequence suggesting that these effectors exploit the host cell’s nuclear import machinery for nuclear translocation.…”
Section: Hold On Tight - Nuclear Pathogen Effectors and The Importin-mentioning
confidence: 99%
“…During invasion of host cells haustoria become enveloped by a highly modified host‐derived membrane, the extrahaustorial membrane (EHM), which separates the haustorium from the host cytoplasm. The EHM provides a pivotal interface for the uptake of nutrients and water from the host and for the delivery of effector proteins secreted by the fungus to manipulate host cells (Bozkurt et al ., ; Caillaud et al ., ). The EHM is continuous with the plant plasma membrane but has a markedly different structure and composition.…”
Section: Introductionmentioning
confidence: 97%
“…Analyses of the subcellular localization of several of these so-called RXLR effectors showed that they can be found in various subcellular compartments (Caillaud et al, 2012a). Each effector seems to have its own specific destination, presumably in the close vicinity of its host target that needs to be modified or (in)activated to suppress host immunity (Caillaud et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%